Efecto de factores genéticos y ambientales sobre el recuento de células somáticas en ganado lechero de Costa Rica - Mora, María Gabriela (2016)
Effect of genetic and environmental factors on somatic cell count of dairy cattle from Costa Rica. The study evaluated the effect of genetic and environmental factors on the Score of Somatic Cell Count [SCS = log2 (SCC/100 000)+3] in Costa Rica dairy cattle. A total of 198 685 daily records from 43 535 lactations, 23 749 cows, 237 herds and 3 breeds were analyzed. A mixed animal model was assessed with zone, herd within zone, breed, number of lactation, month/year or recording, lactation period and daily milk yield as fixed effects; and permanent environment, herd×sire and cow as random effects. Heritability (h2) and repeatability (r) indices for SCS were estimated. Breeding values and reliabilities were estimated for all individuals in the population. The average value of SCS was 3.30 (SD=1.87). All fixed effects were significant. SCS among zones ranged from 3.4 (bh-p) to 3.7 (bmh-p). For herds within zone, SCS ranged from 1.6 to 5.5. SCS increased from 2.7 in first lactation to 4.0 for lactation ≥6. SCS was higher in January (3.6) and lower in April (3.4). A consistent downward trend was observed in SCS from year 2004 (4.3) to 2015 (3.3). A nonlinear pattern was observed in SCS throughout lactation, starting at 3.7, with a marked decrease to a minimum of 3.1 around day 60 postpartum, and a progressive increase to a maximum of 3.9 RESUMEN El estudio evaluó el efecto de factores genéticos y ambientales sobre el Score de Células Somáticas [SCS= log2 (RCS/100 000)+3] en ganado lechero de Costa Rica. Se analizaron 198 685 registros diarios, provenientes de 43 535 lactancias, 23 749 vacas lecheras, 237 hatos y 3 grupos raciales. Se utilizó un modelo animal mixto para evaluar efectos fijos de zona, hato dentro de zona, raza, número de lactancia, mes/ año de registro, periodo de lactancia y la covariable de producción de leche diaria; también para efectos aleatorios de ambiente permanente, hato×semental y vaca. Se calcularon la heredabilidad (h2) y repetibilidad (r) para el Recuento de Células Somáticas (SCS), así como los valores de cría (BLUP) y confiabilidad para los individuos en la población. El promedio de SCS fue 3,30 (DE=1,87) todos los efectos fijos, significativos. Entre zonas, SCS varió desde 3,4 (bh-p) a 3,7 (bmh-p). Para hatos dentro de zona, el SCS osciló entre 1,6 y 5,5. El SCS aumentó desde 2,7 en primera lactancia hasta 4,0 para lactancias ≥6. El SCS fue mayor en Enero (3,6) y menor en Abril (3,4). Se observó un patrón descendente no lineal en SCS desde el 2004 (4,3) hasta el 2015 (3,3) y un patrón no lineal de SCS a lo largo de la lactancia, que inició en 3,7 para disminuir hasta 3,1 al día 60 posparto, mientras que aumentó 3,9 al día 365. Se detectó una reducción de 0,051 en Agronomía Costarricense 40(2): 7-18. ISSN:0377-9424 / 2016 around day 365 postpartum. A reduction of 0.051 in SCS was observed for each increase of 1 kg in daily milk production. Values of h2 and r for SCS were 0.08 (SD=0.008) and 0.33 (SD=0.004), respectively. Breeding values ranged from -1 to +1. Reliabilities of breeding values for cows and bulls were 0.40 (SD=0.16) and 0.44 (SD=0.20), respectively. These results can be used to improve SCS at the herd level, based on prevention in groups under higher risk, optimization of cow culling strategies and improved sire selection.